Coalescence of Porous Coordination Cages into Crystalline and Amorphous Bulk Solids - O'Nolan, Daniel; Sitaula, Paban; Bellamy, Timothy; Chatterton, Lindsey; Amato, Kelly; Todd Ennis, J; Harrison, Sara; Soukri, Mustapha; Blough, Bruce (Inorganic chemistry, 2024)
Discrete porous coordination cages are attractive as a solution processable material whose porosity is not predicated on a network structure. Here, we leverage the peripheral functionalization of these cage structures to obtain 12 novel, solution processable, porous coordination cages that afford crystalline and amorphous single-phase millimeter-scale monolithic bulk structures (six of each) upon solidification. These structures are based upon prototypal metal-organic polyhedra [Cu (5-x-isophthalate) ] (where x = NH , OH), wherein meta-substitution of linker ligands with acyl chloride or isocyanate moieties afforded amide and urethane functional groups, respectively. These porous cage structures were obtainable via direct synthesis between a metal salt and a ligand as well as postsynthetic modification of the cage and formed monoliths following centrifugation and drying of the product. We rationalize their self-assembly as colloidal packing of nanoscale cuboctahedral cages through weak interactions between their hydrophobic alkyl/aromatic surfaces. In general, amorphous solids were obtained via rapid precipitation from the mother liquor upon methanol addition, while crystalline solids could be obtained only following further chloroform and pyridine additions. The structure of the materials is confirmed via gas sorption and spectroscopic methods, while powder X-ray diffraction and transmission electron microscopy are used to determine the nature of these bulk solids.